PERBEDAAN EFEK ANALGESIK AMITRIPTILIN GABAPENTIN DAN PREGABALIN PADA NEUROPATI DIABETIK DAN NEURALGIA TRIGEMINAL - Ibnu Putra,* Yuneldi Anwar,* Khairul Putra Surbakti* (NEURONA, 2018)
INTRODUCTION THE MANAGEMENT OF NEUROPATHIC PAIN IS A CHALLENGE FOR CLINICIANS BECAUSE OF ITS NONSPECIFIC AND DIFFICULT CLINICAL TO TREAT CHARACTERISTICS THE E USE OF ANTIDEPRESSANT DRUGS SUCH AS AMITRIPTYLINE AND ANTICONVULSANTS SUCH AS GABAPENTIN AND PREGABALIN HAS SHOWN VARIOUS EFFICACY OVERCOMING NEUROPATHIC PAIN